Study Of Calculation Of Degaussing System For Reducing Magnetic Field From Submersible Vehicle - Sardono Sarwito; Juniarko Prananda; Eddy Setyo Koenhardono; Anggela Wahyu Kurniawan (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2017)
The rapid development of maritime technology in the world to make Indonesia are also increasingly taking the development of maritime technology, such as in a Submersible Vehicle one is degaussing system, this technology should be owned by the vessel so that the vessel can avoid dangerous explosive equipment contained in the sea. Degaussing system is a system that is in use on the metal parts or electronic devices that are at risk of a magnetic field. This system is used to prevent the vessel from dangerous equipment in the sea which can trigger an explosion and the damage that utilize magnetic fields as a metal-detection sensor when the boat was doing dives. To the authors will plan the design degaussing system, and calculating the system in order to reduce the magnetic properties of the Submersible Vehicle which were obtained by the use of Coil Degaussing along 214,5 meters, a diameter of 0,2, with 500.000 coil that will generate a current of 0,0157 Ampere's 0.0787 Tesla generates a magnetic field.